Peningkatan Aktivitas dan Hasil Belajar Mahasiswa Program Studi Biologi Universitas Negeri Makassar (UNM) pada Mata Kuliah Ekologi Hewan Melalui Pendekatan Konstruktivisme - Hartono, . (Fakultas MIPA UNM, 2011)
This study was done in a classical based method and it aimed to find whether constructivism approach could improve student learning activities and study results. The subjects of the research are the students of biological study programme in Makassar State University who took Animal Ecology Subject in the second semester of 2009/2010 academic year. The research was done in two phases : phase I and phase II. The variables were student learning activities which were obtained through observation and student study results which were obtained from the examination results in the end of each phase. Both results consisted of qualitative and quantitative data which were analyzed descriptively. Based on the result of the research in phase I and phase II we found that there was an improvement in student learning activities and study results significantly. The mean of the examination result increased from 60,10 in phase I to 80,43 in phase II. The percentage of students who achieved grade B (points â‰¥ 76) increased from 5,41% in phase I to 72,97% in phase II. The result shows that constructivism approach in Animal Ecology Study Subject can improve the student learning activities and study results in Biology Study programme of Mathematic and Scientific Faculty of State University of Makassar.